PENGKAJIAN PENERAPAN TEKNOLOGI PENGOLAHAN MANISAN MANGGA KERING DI KABUPATEN INDRAMAYU - D, Histifarina; Agriawati, Deliana P. (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
The Assessment of Technonological Application of Dried Sweet Mango in Indramayu Regency. Mango is one of the horticulture commodities that are seasonal and perishable. To increase the added value and lengthen the storage period as well as to be consumed out of season, mango can be preserved by the use of drying and sugar addition technology. The objective of the assessment is to increase the value of mango fruit by dried mango processing. This assessment was conducted from May 2006 until December 2006 in Kasmaran Village, Widasari District Indramayu Regency by using four mango varieties i.e. Golek, Harumanis, Cengkir and Beruk with raping rate > 80% in collaboration with farmerâs group of Bunga Mawar. The study was carried out by using descriptive method where the four mango varieties were weighed, skimmed, sliced then mixed with sugar and dried. Three major parameters used included physical properties (size, color, others materials and texture), chemical properties (water content, ash content, vitamin C content, sugar content and sulphite residues) and organoleptic properties (color, taste, aromatic, texture and appearance) were measured and the feasibility study was completed. The results showed that dried mango process gave the R/C value 1.65 and B/C value 0.65 and the quality of dried mango resulted from this assessment met the requirement of LITC (Landcaster International Trade Company) USA standard. This means that the fruit has the same physical-chemical characteristics as standard such as color, texture, water content, ash content and sulphite residue, while Beruk mango provided the highest preferences with score > 4 for all parameters.Buah mangga merupakan salah satu jenis komoditas hortikultura yang bersifat musiman dan tergolong perishable (mudah rusak). Untuk meningkatkan nilai tambah buah mangga dan memperpanjang daya simpannya serta dapat dikonsumsi di luar musim, buah mangga dapat diawetkan dengan menggunakan teknologi pengeringan dan penambahan gula. Tujuan pengkajian adalah untuk meningkatkan nilai tambah buah mangga melalui penerapan teknologi pengolahan manisan mangga kering. Pengkajian dimulai dari Mei 2006 hinggga Desember 2006 di Desa Kasmaran, Kecamatan Widasari, Kabupaten Indramayu dengan menggunakan empat jenis mangga yang dipanen pada tingkat kematangan > 80% dengan melibatkan kelompok tani Usaha Bersama Bunga Mawar. Metode pendekatan yang dilakukan yaitu dengan metode deskriptif. Empat jenis mangga yaitu golek, harumanis, cengkir dan beruk ditimbang, dikupas, diiris, ditambah gula dan dikeringkan. Parameter yang diamati meliputi sifat fisik (ukuran, warna, benda asing dan tekstur), sifat kimia (kadar air, kadar abu, kadar vitamin C, kadar gula total dan residu sulfit), sifat organoleptik (warna, rasa, aroma, tekstur dan penampilan) dan analisis kelayakan usaha. Hasil pengkajian, diperoleh nilai R/C sebesar 1,65 atau B/C sebesar 0,65 dengan kualitas manisan buah sesuai standar produk manisan mangga yang dikeluarkan oleh LITCO (Landcaster International Trade Company) USA yaitu dari segi warna, tekstur, kadar air, kadar abu dan residu sulfit, sedangkan dari segi organoleptik mangga jenis beruk memberikan penilaian tingkat kesukaan tertinggi dengan skor > 4 untuk semua parameter.